Cerrado vegetation and global change: the role of functional types, resource availability and disturbance in regulating plant community responses to rising CO2 levels and climate warming - Franco, Augusto Cesar; Rossatto, Davi Rodrigo [UNESP]; Ramos Silva, Lucas de Carvalho; Ferreira, Cristiane da Silva (Brazilian Soc Plant Physiology, 2014)
The cerrado is the most extensive savanna ecosystem of South America and a biodiversity hotspot, harboring a diverse flora ([7,000 species) with high levels of endemism. More than 50 % of the cerrado's approximately 2 million km 2 has been converted into pasture and agricultural lands and it is uncertain how the remaining areas will respond to increasing pressures from land use and climate change. Interactions between disturbance regime and resource (water and nutrient) availability are known to determine the distribution of the various plant communities, of contrasting structure and composition, which coexist in the region. We discuss how fire, nutrients and species traits regulate plant community responses to rising CO2 and global warming, exploring constraints to forest expansion into savanna environments. We describe how climate change will likely reverse a natural process of forest expansion, observed in the region over the past few millennia, accelerating tree cover loss through feedbacks involving fire and resource limitation, and counteracting expected CO2 stimulation effects. These involve changes in fundamental processes occurring above and below ground, which will probably also impact species performance, distribution and biodiversity patterns. We propose a conceptual framework for predicting changes on vegetation structure, highlighting the need for mechanistic models to accurately simulate vegetation dynamics under climate change scenarios. We conclude by explaining why an effective research agenda must necessarily include mitigation efforts, aimed at minimizing impacts of land clearing through enforced conservation and restoration policies in natural and managed ecosystems.
Keywords: Forest-savanna transitions; Grass-tree competition; Savanna; Vegetation-fire dynamics